ISLAM DAN MEDIA SOSIAL: KAJIAN LIVING HADIS DALAM FILM “PAPI DAN KACUNG” DI INSTAGRAM - Ihsan Nurmansyah (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2019)
This paper discusses the study of living hadith in the film “Papi dan Kacung” (read: PdK) episodes 5-7 uploaded by Qoryyan on Instagram in 2018. The film "PdK" is a short Islamic film with a duration of about 2 minutes and in every the scene shows the reception of the Prophet's hadith, especially about the guidance of doing good. Therefore, to find out the variety of receptions on the Prophet’s hadith in the film “PdK” episodes 5-7 by using the reception theory introduced by Ahmad Rafiq. The results of this study are 1) exegesis reception manifested in the reading of the Book Riyadhus Shalihin; 2) aesthetic reception contained in the reading of the Book Riyadhus Shalihin accompanied by a Zamzam back sound; 3) functional reception on the informative aspect, which is to care for orphans, the virtue of saying greetings, comparison of world life and the hereafter. Whereas the function on the performative aspect, namely Kacung always follows his Papi advice in the form of saying "Assalamu'alaikum warahmatullah wabarakatuh", saying istighfar "Astaghfirullahal adzhim” and wanting to be a good and useful person.